Perbedaan Pemahaman Konsep Sistem Koloid Antara Pembelajaran Menggunakan Peta Konsep Dengan Peta Pikiran Pada Siswa Kelas XI MIPA MAN Kota Palangka Raya Tahun Ajaran 2018/2019 - Ayu Kristina (Jurnal Ilmiah Kanderang Tingang, 2020)
Many students have difficulty understanding the concept of a colloidal system. The purpose of this study was to describe the differences in understanding of the concept of colloidal systems between learning using concept maps with mind maps in students of class XI MIPA MAN in Palangka Raya city 2018/2019 school year. This research is a quantitative research. The sample in this study were 52 students of MIPA MAN Class Palangkaraya City. The instrument used was a concept understanding test (pretest, posttest) and student worksheets. The results of data analysis using the Mann Whitney test showed that there were differences in understanding colloidal system concepts between students who learned to use concept maps and students who learned to use mind maps. The average post-test scores of concept map class students (85.40%) are higher than the average post-test scores of mind map classes (71.53%).